The Influence of Teacher’s Certification and Motivation on the Teacher’s Performance - Antoni, Antoni; Fitria, Happy; Ahyani, Nur (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to analyze the effect of certification and motivation on teacher’s performance. The location of this research was carried out at a public high school in the Kayuagung District. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all teachers in public high schools in the Kayuagung District, consisting of 87 teachers. data collection technique using a questionnaire. Data analysis techniques using quantitative descriptive analysis techniques, and multiple regression. The results of this study state that 1) there is a significant influence between school teacher’s certification on the performance of public high school teachers in the Kayuagung District; 2) there is a significant influence between motivation on the performance of State Senior High School teachers in the Kayuagung District; 3) there is a significant effect of teacher’s certification and motivation together on the performance of teachers in public high schools in the Kayuagung District. These results suggest that the higher the qualification of a certified teacher, the higher the performance. Then, motivation within the teacher will have an impact on teacher’s performance.